Pengaruh penggunaan model read question answer terhadap keaktifan mahasiswa dalam berdiskusi pada mata kuliah mikologi - Farida Nurlaila Zunaidah; Tutut Indah Sulistiyowati (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2020)
The low activity of students in discussing mycology courses is caused by the lack of use of innovative learning models. The research purpose was to determine the effect of using the Read Question Answer (RQA) model on student activeness in discussing mycology courses.This research uses quantitative research methods with a quasi-experimental research type through a one-group pretest-posttest research design. The research instrument used was a student activity questionnaire. Research data is the average value of student activity. The research data analysis technique used the dependent paired sample t-test. The results showed that there was an effect of using the RQA model on student activeness in discussing mycology courses. This is evident from the t-count value is greater than the t-table (7.15 > 2.23). The conclusion of this research is the use of the RQA model affects student activeness in discussing mycology courses.